2017
DOI: 10.7860/jcdr/2017/27171.10237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic Stewardship Program on Prescribing Pattern of Antimicrobials in Patients of Medical Intensive Care Unit

Abstract: In-depth analysis of the study revealed a positive impact of ASP and antibiotic policy. Implementation of ASP in year 2013, brought an effective increase in the appropriate use of antimicrobials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…AMS is a set of coherent activities that results in responsible use of antibiotics, with the definition of responsible use being context-specific and updated periodically ( 3 ). The role of AMS in a healthcare facility has been demonstrated through various studies ( 4 6 ). These studies show significant reduction in use of antimicrobials, expenditure associated with antimicrobial use and levels of resistance among various indicator pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…AMS is a set of coherent activities that results in responsible use of antibiotics, with the definition of responsible use being context-specific and updated periodically ( 3 ). The role of AMS in a healthcare facility has been demonstrated through various studies ( 4 6 ). These studies show significant reduction in use of antimicrobials, expenditure associated with antimicrobial use and levels of resistance among various indicator pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Still, we recognise low/middle-income countries (LMIC) face ASP implementation challenges including limited diagnostic laboratory capability, inadequate awareness, limited access to quality antibiotics and high patient census 15. To date, few studies have explored the challenges facilities in India face carrying out ASPs, such as less available manpower and money dedicated to maintaining a detailed electronic medical record (EMR) compared with higher-income country counterparts 16–18. EMR systems have been found to be one of the most effective ways of keeping records on patient care and allow for easier discussion and feedback on antibiotic choices 17.…”
Section: Introductionmentioning
confidence: 99%
“…14 An Indian study showed that 93.3% of the antibiotic use in ICU was for therapeutic use and 89.3% antimicrobial prescriptions were adherent to the hospital antibiotic policy. 15 A prospective observational study found antibiotic use longer than the recommended duration (33.3%) and use in non-infectious conditions (32.4%). 16 In yet another study, 64.1% of prescriptions were appropriate which increased to 77.4% after a 12 month follow up.…”
Section: Discussionmentioning
confidence: 99%